PENGARUH ANIMASI TERHADAP MOTIVASI DAN HASIL BELAJAR IPA - Alvainy Hayatut Darojah; Ihwan Firmansyah; Zainal Arifin (JURNAL PENELITIAN BIDANG PENDIDIKAN, 2022)
The learning motivation among students in each learning activity plays a significant role in enhancing student learning achievement in certain subjects. Seeing students less enthusiastic in the learning process, the researcher tried to make learning videos, namely using Animation Videos which were expected to help students become motivated triggering them more enthusiastic in learning. This research is a type of quantitative research, as for the design carried out in this study is true experimental with the type of Pretest-Posttest control group design. Pretest was employed to determine the learning motivation of students, whereas the posttest was used to determine student learning achievement at the end of learning. The data analysis technique in this study used a validity test, reliability test, normality test, and Manova. Based on the results of the Cronbach reliability test, it can be interpreted that the questionnaire is reliable. Based on the output of the normality test, it is known that the significant value is greater than 0.05. Therefore, it can be concluded that the questionnaire questions are normally distributed. According to the Manova test, it is known that the value is less than 0.05, which can be concluded that there is a significant effect of using Animation Videos learning media on interest and learning achievement.